Prehensile Manipulation Planning: Modeling, Algorithms and Implementation - Lamiraux, Florent; Mirabel, Joseph (IEEE transactions on robotics, 2022)
This article presents a software platform tailored for prehensile manipulation planning named humanoid path planner. The platform implements an original way of modeling manipulation planning through a constraint graph that represents the numerical constraints that define the manipulation problem. We propose an extension of the RRT algorithm to manipulation planning that is able to solve a large variety of problems. We provide replicable experimental results via a docker image that readers may download to run the experimental results by themselves.